Cognitive and Behavioral Challenges in Responding to Climate Change - Norgaard, Kari Marie (Washington, DC: World Bank, 2012)
Climate scientists have identified global warming as the most important environmental issue of our time, but it has taken over 20 years for the problem to penetrate the public discourse in even the most superficial manner. While some nations have done better than others, no nation has adequately reduced emissions and no nation has a base of public citizens that are sufficiently socially and politically engaged in response to climate change. This paper summarizes international and national differences in levels of knowledge and concern regarding climate change, and the existing explanations for the worldwide failure of public response to climate change, drawing from psychology, social psychology and sociology. On the whole, the widely presumed links between public access to information on climate change and levels of concern and action are not supported. The paper's key findings emphasize the presence of negative emotions in conjunction with global warming (fear, guilt, and helplessness), and the process of emotion management and cultural norms in the construction of a social reality in which climate change is held at arms length. Barriers in responding to climate change are placed into three broad categories: 1) psychological/conceptual, 2) social and cultural, and 3) structural (political economy). The author provides policy considerations and summarizes the policy implications of both psychological and conceptual barriers, and social and cultural barriers. An annotated bibliography is included.